2022
DOI: 10.1021/acsnano.2c01153
|View full text |Cite
|
Sign up to set email alerts
|

Bright, Magnetic NIR-II Quantum Dot Probe for Sensitive Dual-Modality Imaging and Intensive Combination Therapy of Cancer

Abstract: Improving the effectiveness of cancer therapy will require tools that enable more specific cancer targeting and improved tumor visualization. Theranostics have the potential for improving cancer care because of their ability to serve as both diagnostics and therapeutics; however, their diagnostic potential is often limited by tissue-associated light absorption and scattering. Herein, we develop CuInSe2@ZnS:Mn quantum dots (QDs) with intrinsic multifunctionality that both enable the accurate localization of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 76 publications
2
65
0
Order By: Relevance
“…NIR-II fluorescence can achieve good imaging resolution even for deep tissue penetration, which makes it promising for providing information with high physiological and pathological relevance. [14,24,38] In 2009, the use of light-emitting single-wall carbon nanotubes to perform in vivo NIR-II imaging of tumor vessels beneath the skin of mice constituted one of the first steps in making use of NIR-II window for biological imaging. [24] Pioneering SNC-based NIR-II fluorescence imaging studies were based on Ag 2 S SNCs, [47,83] and demonstrated high signal-to-noise ratio for in vivo imaging.…”
Section: Nir-ii Fluorescence Imagingmentioning
confidence: 99%
See 4 more Smart Citations
“…NIR-II fluorescence can achieve good imaging resolution even for deep tissue penetration, which makes it promising for providing information with high physiological and pathological relevance. [14,24,38] In 2009, the use of light-emitting single-wall carbon nanotubes to perform in vivo NIR-II imaging of tumor vessels beneath the skin of mice constituted one of the first steps in making use of NIR-II window for biological imaging. [24] Pioneering SNC-based NIR-II fluorescence imaging studies were based on Ag 2 S SNCs, [47,83] and demonstrated high signal-to-noise ratio for in vivo imaging.…”
Section: Nir-ii Fluorescence Imagingmentioning
confidence: 99%
“…[179] Alongside with developments of imaging instrumentation for efficiently collecting NIR-II emission signals, NIR-II emitting SNCs were used to portray structures of living tissues, including vascular system, lymphatic system, and tumors. [12,13,38,46] By using PEGylated Ag 2 S SNCs with a long blood circulation time as the contrast agent, peripheral vasculature (≈100 µm in size) was visualized in vivo at a micro meter-scale resolution, which holds great potential for real-time imaging of those structures when dealing with vascular-related diseases. [46] In the same study, PEGylated Ag 2 S SNCs were also used for imaging lymphatic vessels (≈100 µm in size) and lymph nodes (≈950 µm in size), and the clarity and penetration depth were significantly improved compared with ICG dye, a standard contrast agent for clinically guided sentinel-lymph-node resection, which can help to guide the surgeries more precisely for their identification and dissection.…”
Section: Nir-ii Fluorescence Imagingmentioning
confidence: 99%
See 3 more Smart Citations